O método de interpretação da escritura no Tratado Teológico Político de Spinoza - Dantas, Ivonaldo Correia (2013)
The purpose of this dissertation is to present the method of Scriptural interpretation described in the seventh chapter of the Theological-Political Treatise. According to its preface, Spinoza describes a new and free method of Scriptural interpretation, from which he investigates the issues relative to this interpretation, and that, throughout his argument, leading him to conclude in favor of the absolute freedom of reason and the separation between philosophy and theology. The method for the interpretation of Scripture allows to develop all the arguments necessary for the reader accept the conclusion of the Spinoza s Treatise, that freedom of thinking is beneficial to the state and the religion itself. For Spinoza, the method is an instrument that uses the mind to investigate the truth. The method for the interpretation of Scripture is the same for the interpretation of nature, as Spinoza says. The method requires certain requirements which the reader of the Treatise must be followed to properly interpret Scripture. The first requirement is the criterion of ex sola Scriptura, in others words, only accept information extracted from Scripture itself and its history. The object and the criteria of the method focus on Scripture, so over several chapters, the Treatise shows that many things that claim of Scripture are just prejudices. In the interpretation of Spinoza, the interpreter is revealed in another role, that of researcher. Before it was a usurper, when the performers took advantage of the prejudices of the vulgar to usurp the meaning of the biblical texts for their own benefit. The interpretive question of Spinoza focuses on the meaning and not the supposed truth of the texts. Then, the old pressuposition, that the Revelation contained in sacred texts guarantees the narrations truth, is entirely abandoned. Spinoza establishes a new presupposition: the appropriate knowledge for the language and the history of the text. Using the same method for the interpretation to the nature and to the Scripture, the philosopher demonstrates that they underlie distinct sciences, respectively, philosophy and theology, and that both are distinct from each other and that do not submit to one another. Therefore, since only the actions of men are the reason for his social judgment, free thinking is not only lawful but beneficial.